PENDIDIKAN ISLAM DI PONDOK PESANTREN AL-HASANIYAH PERSPEKTIF ISLAM NUSANTARA - Lina Nashirotul Ummah An-noer; Ilman Nafia; Suklani Suklani (CV. ADIBA ASIHA AMIRA, 2025)
Islamic education in Indonesia has a unique characteristic, namely the ability to adapt to local cultures without losing Islamic values, as seen in the concept of Islam Nusantara. Through this approach, Islam has been widely accepted in Indonesia, especially through the role of Walisongo, who utilized various cultural media, such as arts and Islamic boarding schools (Pondok Pesantren). Pondok Pesantren Al-Hasaniyah in Kedawon Brebes is one such institution that integrates Islamic teachings with local culture through the Islam Nusantara concept. This study aims to describe and analyze the concept of Islamic education at Pondok Pesantren Al-Hasaniyah from the Islam Nusantara perspective using a qualitative descriptive method, with data collected through interviews and documentation. The findings reveal that Pondok Pesantren Al-Hasaniyyah implements Islamic education oriented toward Nusantara values. Values such as mutual cooperation (gotong royong), simplicity, and tolerance are consistently practiced to shape students who are religious, independent, and tolerant. Additionally, national values are taught to instill a spirit of nationalism among students. Aswaja principles such as tasamuh (tolerance), tawazun (balance), and tawasuth (moderation) serve as the primary guidelines in shaping students’ character, enabling them to coexist harmoniously in a diverse society.